Urgensi Perjanjian Perkawinan Pasca Putusan Mahkamah Konstitusi Nomor 69/PUU-XIII/2015 - Istiqomah; Jumni Nelli (MASADIR: Jurnal Hukum Islam, 2025)
This study discusses the urgency of prenuptial agreements following the Constitutional Court Decision No. 69/PUU-XIII/2015, which amended the timing provisions for the creation of prenuptial agreements under Law No. 1 of 1974 concerning Marriage. This research employs a literature-based method with a normative juridical approach, examining statutory regulations, Constitutional Court decisions, and relevant legal literature. The findings reveal that the Court's decision provides legal flexibility for married couples to enter into marital agreements during the course of their marriage, thereby enhancing legal protection, ensuring legal certainty, and preventing potential domestic conflicts. However, in practice, there remains a need for clearer technical regulations and broader public dissemination. This study concludes that post-decision marital agreements hold significant urgency as a legal protection instrument within the household.